Students’ representations of education quality in different school levels: An exploratory study with Portuguese students - Cid, M.; Bonito, J.; Oliveira, M.; Saraiva, M.; Rebelo, H. (EDULEARN09 Proceedings, 2009)
Quality may be studied from different perspectives. Research shows that many variables may be involved when the target is the educational system. One may analyse the motivation of students and teachers, the methodologies of teaching, the processes of evaluation, the resources available, the educational facilities, the course organization or the academic success. Recent research results show a strong positive correlation between students’ academic success and the quality of education available to them. However, the way students perceive the quality indicators has been a less explored area. We present the results of an academic longitudinal research project that aims to study the students’ representations of quality along the school system in order to contribute to an improvement of teaching and learning processes. In particular, the focus of discussion is based on the representations of students in three different moments of their school life: 9th grade, 12th grade and early higher education. The sampling of this exploratory study focused on compulsory education and secondary education in two cities from rural and urban spaces of Évora district. It further encompassed courses of three institutions of higher education in Portugal: the University of Évora, the Polytechnic Institute of Beja and the Polytechnic Institute of Portalegre. Data collection was done through a questionnaire survey.